2016
DOI: 10.1007/s00300-016-1950-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of bivalve larvae within a high Arctic fjord

Abstract: The temporal and spatial distribution of larval plankton of high latitudes is poorly understood. The objective of this work is to identify the occurrence and abundance of pelagic bivalve larvae within a high Arctic fjord (Adventfjorden, Svalbard) and to reveal their seasonal dynamics in relation to environmental variables-temperature, salinity and chlorophyll a-between December 2011 and January 2013. We applied a combination of DNA barcoding of mitochondrial 16S ribosomal RNA and morphological analysis to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…Our study is among the first for Arctic meroplankton to supplement the morphological identification of meroplankton with molecular barcoding to better resolve taxonomic diversity of larvae. Our lab protocol resulted in a much higher success rate (>90%) than in previous attempts, where it did not exceed 20-50% (e.g., Webb et al, 2006;Heimeier et al, 2010;Brandner et al, 2017), and we hope that our effective, simple identification protocol will pave the way for future biodiversity studies of meroplankton.…”
Section: Advances and Challenges Of Studying Meroplankton Using Molecmentioning
confidence: 75%
See 2 more Smart Citations
“…Our study is among the first for Arctic meroplankton to supplement the morphological identification of meroplankton with molecular barcoding to better resolve taxonomic diversity of larvae. Our lab protocol resulted in a much higher success rate (>90%) than in previous attempts, where it did not exceed 20-50% (e.g., Webb et al, 2006;Heimeier et al, 2010;Brandner et al, 2017), and we hope that our effective, simple identification protocol will pave the way for future biodiversity studies of meroplankton.…”
Section: Advances and Challenges Of Studying Meroplankton Using Molecmentioning
confidence: 75%
“…The high variability between locations and sampling years is a consequence of the inherently patchy distribution of larvae in time and space, due to the limited larval duration and episodic reproduction events in many benthic organisms (Shanks, 2009). For example, the exceptionally high abundance of barnacle larvae observed in 2004 was likely due to the earlier timing of the sampling by 3-4 weeks that year compared to other years, as in other Arctic regions, peak abundances of barnacle larvae have been recorded early in the summer (Brandner et al, 2017;Michelsen et al, 2017). A study on decapod larvae in the Chukchi Sea spanning two consecutive years similarly found abundances to differ over several orders of magnitude, which the authors explain by the slightly different timing of the cruises (Landeira et al, 2017).…”
Section: Diversity and Distribution Patterns Of Meroplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is an important contribution to the scarce current knowledge on the reproductive strategies of marine invertebrates in the Arctic Ocean (Poltermann et al 2000;Fetzer and Arntz 2008;Søreide et al 2010;Kuklinski et al 2013;Brandner et al 2017). The reproductive traits and dynamics of polar benthic invertebrates are fundamental to understand these ecosystems and their resilience in the face of ongoing climate change.…”
Section: Discussionmentioning
confidence: 99%
“…However, a different perspective, based on developmental modes and energy requirements of larval stages rather than on adult food necessities, suggests that polar invertebrates with planktotrophic larvae may reproduce coupled to phytoplankton blooms, while brooders or those with lecithotrophic larvae may be decoupled from primary production pulses and reproduce year-round (Pearse et al 1991). Different strategies have been described for polar marine invertebrates; however, most of the available information is based on Antarctic species (i.e., Clarke 1996; Barnes and Clarke 1998;Chiantore et al 2002;Orejas et al 2002;Grange et al 2004Grange et al , 2007Grange et al , 2011Sahade et al 2004b;Brockington et al 2007;Servetto et al 2013;Servetto and Sahade 2016), and data for Arctic species are scarce (Poltermann et al 2000;Brandner et al 2017).…”
Section: Introductionmentioning
confidence: 99%